Optimal Measurement of Visual Transmission Design Based on CAD and Data Mining - Wu, Wenchao; Yusoff, Irwan Syah Md; Alli, Hassan Bin Hj; Wang, Qi (CAD Solutions, LLC, 2024)
This study aims to build a complete visual transmission design optimization measurement system by integrating CAD (Computer-aided design) and DM (Data mining) technologies. Specifically, this article first uses CAD technology to model and quantitatively analyze the visual design elements accurately and then extracts the key factors and laws that affect the design effect from a large quantity of design data through DM. Finally, combining the results of CAD and DM, a scientific and effective optimization scheme is proposed, and experiments verify its feasibility and effectiveness. Experiments show that users often show higher stay time and more frequent interaction behavior when facing attractive design elements. Moreover, users have a positive attitude toward innovative and personalized design elements; Bright colors and dynamic visual effects are outstanding in attracting users’ attention. This study is expected to provide more accurate and efficient optimization measurement methods for visual transmission design and promote innovation and development in this field.